Clinicopathologic and genetic evaluation of B-lymphoblastic leukemia with intrachromosomal amplification of chromosome 21 (iAMP21) in adult patients. Issue 13 (10th November 2022) - Zak, Taylor; Gao, Juehua; Behdad, Amir; Mehta, Jayesh; Altman, Jessica K.; Ji, Peng; Lu, Xinyan; Sukhanova, Madina
Abstract: Intrachromosomal amplification of chromosome 21 (iAMP21) defines a rare provisional entity of B-cell acute lymphoblastic leukemia (B-ALL) in the current WHO classification and has been described as specific for pediatric patients with a median age at diagnosis of 9–10 years. We report two adult cases of B-ALL with iAMP21, one 31-year-old woman and one 40-year-old man, identified by karyotyping and next generation sequencing (NGS), with fluorescence in situ hybridization (FISH) pattern meeting diagnostic criteria for iAMP21. Both patients were treated on high-risk chemotherapeutic regimen followed by stem cell transplant. In contrast to reported high relapse rate within the first three years in pediatric population, our adult patients are alive in remission, with the interval from diagnosis to last follow up of 2.95 and 3.96 years. Our cases illustrate the importance of screening for iAMP21 in adult population when ETV6-RUNX1 FISH testing is not routinely performed for adult patients.